Atypical lipomatous tumor of the oropharynx: A case report - Anna Pamela C. Dela Cruz; Patricia Ann U. Soriano; Cesar Vincent L. Villafuerte III; Ruter M. Maralit; Michele H. Diwa (Clinical Case Reports, 2022)
Abstract Atypical lipomatous tumor or well‐differentiated liposarcoma is a rare condition in the laryngopharynx. We present a case of a 63 year‐old male with progressive dysphagia who later manifested with a mass that regurgitates outside the oral cavity. Surgical removal was done via a transoral approach, followed by adjuvant radiotherapy.